(3eUHGM GdCfGe aj TQM TQGjY GdESdGes - (3GdHOjQj, GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3bhdg cJGH GdbVGA ; Cbhd GdCUd ajg bHd GdGLJeGY GdcJGH hGdSfI bGd Gddg JYGdi (B{ (3jG OGhO EfG LYdfGc NdjaI aj GdCQV aGMce Hjf GdfGS HGdMb (B...s
(3BNQgG (B:s
.. (3haj TehdgG cPdc GdMGd hGdCUd YOe GdKHhJ eG de jJe ELeGY HeNUhU GdebGe Ydi NdGaI (B.. (3cGfJ GdOYhi HGdOjI adG QjH (B... (3hGddg GdYGdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\ 121s
(3GdPQjYI (B21\4132s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis